基于轮体形式及传动结构的齿轮传动创新发展研究 - 庞志锋; 张春林; 杨建鑫; 赵自强 (Jixie chuandong)
In order to promote the innovative progress of gear transmission,the concepts of gear body form and transmission structure are systematically summarized and scientifically depicted.The characteristics,development course and research status of various kinds of gear body form,tooth profile and transmission structure are detailedly reviewed and discussed.According to gear transmission principles,it is indicated that the innovation of gear body form and transmission structure is essential route of innovative progress of gear transmission.Furthermore,the compounding and match innovation strategy of gear transmission is propounded;the keystones of innovative research are generalized,and the direction of innovative progress is pointed out.